A study of parental satisfaction towards the early childhood education administration of the Child Development Center under Non Puei Subdistrict Administrative Organization, Kut Chum District, Yasothon Province: A study of parental satisfaction towards the early childhood education administration of the Child Development Center under Non Puei Subdistrict Administrative Organization, Kut Chum District, Yasothon Province - Boonsam, Chalida; Tieangtam, Churat; Moonsarn, Baramee; Prakhu Akutarasatatikoon; Wangphon, Ploychanokwan (RATANABUTH JOURNAL, 2023)
The objectives of this research were 1) to study the parents' satisfaction with the early childhood education administration of the Child Development Center under Non Puei Subdistrict Administrative Organization, Kut Chum District, Yasothon Province 2) to compare the parents' satisfaction. on the early childhood education administration of the Child Development Center under Non Puei Sub-district Administrative Organization, Kut Chum District, Yasothon Province. 2022, there were 79 people. The tool for collecting data was a questionnaire. The data were analyzed by using frequency distribution statistics by showing numbers and percentages (Percentage) and analyzing the level of decision-making behavior for the President of Yasothon Provincial Administrative Organization using the mean (Mean) and standard deviation (Standard Deviation). ) and statistics used to test the hypothesis. Sex classification was t-test (independent). The results of the analysis of parental satisfaction towards the early childhood education administration of the Child Development Center under Non Puei Subdistrict Administrative Organization, Kut Chum District, Yasothon Province were generally at a high level. And when considering each aspect, it was found that the satisfaction of parents was at a high level in all 4 aspects. The highest average was the teacher, followed by the facilitation and other services. for the arrangement of experiences and teaching and learning activities, and for the environment, respectively. Non Puei Sub-District Administrative Organization, Kut Chum District, Yasothon Province found that male and female satisfaction were not different.